Fatigue life evaluation of aged rails focusing on the state of hanging sleepers and rail-head surface irregularities that affect rail stress - Mitsuru HOSODA; Nobutaka TAKAHASHI; Tadashi DESHIMARU (Nihon Kikai Gakkai ronbunshu)
In this study, we focused on hanging sleepers and rail-head surface irregularities, which are considered to affect the fatigue life of aged rails, and statistically analyzed their occurrence on commercial lines. The occurrence of these conditions was expressed by the probability density function, which confirmed that the gamma distribution fits well. In addition, fatigue tests were conducted on aged rails, where these conditions were significantly present. Aged rail bending fatigue tests (cumulative passing tonnage: 800 million tons) were conducted, and significant hanging sleepers and rail-head surface irregularities were observed. It was confirmed that the fatigue strength of the rail at the end of the current replacement cycle is equivalent to that of the previously tested aged rail (cumulative passing tonnage: 540 million tons). It is expected that the replacement cycle can be further extended if the hanging sleepers and rail-head surface irregularities are below a certain value. The study also proposed a probabilistic safety evaluation method and control values for the long-term use of rails. The rail health index, calculated from the rail bottom bending stress and fatigue limit, was proposed as an index for preventing rail breakage at locations where significant hanging sleepers and rail-head surface irregularities occur when the cycle replacement is extended or eliminated.